Kompozit rezin materyallerin farklı ışık kaynaklarıyla polimerizasyonu sırasında oluşan ısısal değişikliklerin incelenmesi - Arife Dogan; Hakan Demir; İhsan Hubbezoglu; Orhan Dogan (Cumhuriyet University, 2011)
Purpose: This in vitro study investigated the effect of three light curing units on the temperature rise under 2 mm thick dentin during polymerization of different resin composite materials. Material and Methods: Three different light sources were used: A conventional halogen lamp (QTH), a plasma arc (Apollo 95E Elite) and a light-emitting diode (LED) light curing units. 90 dentin discs in 8 mm diameter and 2 mm thickness were obtained from freshly extracted premolar teeth. Fifteen disc-shaped specimens from each resin composite material (Admira, Filtek 60, Premise, Tetric Flow, Tetric Ceram and Filtek 250), 6 mm in diameter and 2 mm in depth, were placed on dentin discs in teflon molds (n=5). The specimens were irradiated with Standard mode of each light curing unit. A type-L thermocouple wire (Fe-Const.) connected to data logger (E-680) was used to record temperature rise which under dentin during polymerization by three different light sources. Data were analyzed by two-way ANOVA and Tukey tests. Results: Among all light curing units, the highest temperature rise was recorded with use of the halogen LCU, and the LED irradiation led to the lowest temperture rises. The highest temperature rise was observed for Admira and Tetric Flow resin composites, whereas the lowest temperature rise was for Premise. Conclusion: In all conditions tested, the temperature elevations were found to be lower than the critical value for pulpal injury reported in literature. Therefore, the LCUs used in this study could be safety for clinical situations mentioned before.   ÖZET Amaç: Bu in vitro çalışma üç farklı ışık kaynağının farklı rezin kompozit materyallerin polimerizasyonu sırasında 2 mm dentin altında oluşan ısı artışına etkisini araştırdı. Gereç ve Yöntem: Üç farklı ışık cihazı, bir halojen (QTH), bir plazma ark (Apollo 95E Elite) ve bir light-emitting diode (LED) kullanıldı. Yeni çekilmiş premolar dişlerden 8 mm çapında ve 2 mm kalınlığında 90 adet dentin disk hazırlandı. Her bir rezin kompozit materyalden (Admira, Filtek 60, Premise, Tetric Flow, Tetric Ceram and Filtek 250), 6 mm çap ve 2 mm derinlikte 15 örnek teflon moldda dentin üzerine yerleştirildi (n=5). Örnekler her bir ışık kaynağının standart modu ile polimerize edildi. Üniversal Girişli Gelişmiş Tarayıcı / Alarm Cihazına (E-680, Elimko Co., Turkey) bağlı bir Ltipi termokapl kablosu (Fe-Const.) polimerizasyon sırasında dentin altındaki ısı değişimlerini kaydetmek için kullanıldı. Veriler iki-yönlü varyans analizi ve Tukey testle değerlendirildi. Bulgular: Tüm ışık kaynakları arasında en yüksek ısı artışı halojen ışık kaynağı kullanımı ile kaydedilirken LED irradiasyon en düşük ısı artışına neden oldu. En yüksek ısı artışı Admira and Tetric Flow kompozitlerde gözlemlenirken, en düşük ısı artışı Premise için belirlendi. Sonuç: Test edilen tüm koşullarda ısı artışları pulpa hasarı için literatürde bildirilen kritik değerin altında bulundu. Dolayısıyla test edilen bu ışık kaynakları önceden belirtilen klinik koşullarda güvenle kullanılabilir. Anahtar kelimeler: Kompozit, polimerizasyon, ısı artışı